Cognitive Fatigue Among Santri in Dual-Curriculum Islamic Boarding Schools - Rohani Rohani; Muhammad Ali Gunawan; Camila Fatah Suroyya; Suciptono (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Cognitive fatigue has emerged as a critical concern in educational settings that require sustained mental effort, particularly in Islamic boarding schools implementing dual-curriculum systems. Santri are required to balance intensive Qur’anic memorization with formal general education, creating substantial cognitive demands that may affect learning effectiveness and mental well-being. This study aims to examine the level of cognitive fatigue among santri and to identify key contributing factors within a dual-curriculum pesantren context. A quantitative descriptive design was employed involving 120 students aged 13–18 at Darul Iman Islamic Boarding School, North Lombok, Indonesia. Data were collected using the Pediatric Cognitive Fatigue Scale (PCFS), supported by classroom observations and analysis of study duration, sleep patterns, and memorization load. The findings indicate that most students experience moderate to high levels of cognitive fatigue. Fatigue levels were strongly associated with prolonged daily study time exceeding ten hours, reduced sleep duration, and high Qur’anic memorization intensity, while gender and age were not significant predictors. These results highlight the cumulative cognitive risks of extended academic engagement without adequate rest. This study contributes to the limited empirical literature on student cognitive fatigue in religious education environments. The findings imply the need for pesantren administrators and policymakers to redesign learning schedules by incorporating structured rest periods, balanced memorization targets, and sleep protection strategies to promote healthier and more sustainable learning environments for adolescents in dual-curriculum Islamic boarding schools.